Pendampingan Manajemen Keuangan, TTG dan Strategi Pemasaran Digital pada UMKM Batik Ecoprint F2P dan Artaka Art of Shibori Surabaya - Dewi Sutjahyani; Siti Mujanah; Riyadi Nugroho; Adistyasyah Bagus; Alifia Salma Nabila; Naufal Dzaki Abdullah Abdull (Jurnal Pengabdian Masyarakat, 2025)
This community partnership program (PKM) is carried out to strengthen the sustainability of the business of Batik Ecoprint F2P and Artaka Art of Shibori MSMEs in Surabaya. These two MSMEs have great potential in producing distinctive environmentally friendly products, but still face challenges in terms of production equipment, business management, and digital marketing. Through mentoring involving lecturers and students of the University of August 17, 1945 Surabaya, this activity provides solutions in the form of financial management training, natural coloring technique training, digital marketing strategies, and procurement of appropriate technology (TTG). The results of the activity show that partners have increased their capacity in producing batik efficiently, managing their business professionally, and marketing their products to a wider market, both offline and online. The real impact of this program can be seen in the increasing enthusiasm of housewives in entrepreneurship and the growing awareness of the importance of protecting the environment. This activity not only strengthens the position of MSMEs in the local economy, but also serves as a means of implementing the Main Performance Indicators (KPIs) of universities through the active involvement of students and lecturers in off-campus activities. Overall, a collaborative and contextual approach has proven effective in supporting the independence of MSMEs based on local wisdom and environmental sustainability.